FEM simulation of triple diffusive natural convection along inclined plate in porous medium: prescribed surface heat, solute and nanoparticles flux - Goyal, Mania; Goyal, Rangoli; Bhargava, Rama (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, triple diffusive natural convection under Darcy flow over an inclined plate embedded in a porous medium saturated with a binary base fluid containing nanoparticles and two salts is studied. The model used for the nanofluid is the one which incorporates the effects of Brownian motion and thermophoresis. In addition, the thermal energy equations include regular diffusion and cross-diffusion terms.
Keywords: triple diffusive; natural convection; nanofluid; binary base fluid; porous medium; solutal concentration flux; nanoparticle concentration flux; inclined plate